A giant darter (Pelecaniformes: Anhingidae) from the Upper Miocene of Argentina and weight calculation of fossil Anhingidae - Areta, Juan Ignacio (2007)
Darters are fresh-water birds presently distributed in tropical regions all over the world. Fossil darters were only known from North America, Europe, and Africa, but description in the last decade of various genera and paleospecies revealed an unsuspected diversity of large-bodied taxa of Anhingidae in the Tertiary of South America. We report the finding of the largest specimen of Anhingidae known to date, for which we estimate a mass of 17.7 kg. Specific assignment is precluded both on morphological and stratigraphical grounds. We tentatively assign this form to the genus cf. Giganhinga. The non-monophyletic "Miocene radiation of giant darters" is set in perspective, showing the existence of both dwarf and giant forms. The femur in birds is usually little influenced by locomotion and feeding adaptations, which makes it the best hindlimb element to predict body-weight. Due to the existence of flightless forms, we recommend caution when estimating mass from fore-limbs in the fossil anhingas.